Surveying for civil and mine engineers: Acquire the skills in weeks - Walker, John; Awange, Joseph (Springer, 2020)
This updated and expanded edition of the book includes four additional chapters on earthwork on sloping sites; transitional curves and super elevation; calculations of super elevations on composite curves; and underground mine surveying. Richly illustrated with diagrams, equations and tables as well as examples of every day survey tasks. It also covers new topics, such as the global navigation satellite system’s (Real Time Kinematic-RTK), which are increasingly used in a wide range of everyday engineering applications.